ANALISIS PERFORMA ENGINE MARCHETTI SF 260 - Rabeta, Bismil (JTK: JURNAL TEKNOLOGI KEDIRGANTARAAN, 2019)
The Aerospace Air Marshal Surydarma University   (Unsurya) is a college   of movement in aerospace technology that attempts to contribute and information related to aviation technology. One of the facilities owned by Unsurya is the Marchetti SF-260 aircraft which is used as a practice facility for implementing ground run-up engine tests. As long as this aircraft is in Unsurya, no one has ever tried to analyze the engine's performance. Therefore in this study do an analysis of the performance of the marchetti aircraft SF-260 was carried out using the Lycoming O-540 E4A5 engine to determine engine torque, engine power and mechanical efficiency varied by cruising altitude. From the results of the analysis it was found that the highest value at torque was 480.24 Nm, engine power 182 BHP and mechanical efficiency 42.83% obtained at an altitude of 10,000 ft.